Pilot trial of K562/GM-CSF whole-cell vaccination in MDS patients. Issue 12 (2nd December 2018) - Robinson, Tara M.; Prince, Gabrielle T.; Thoburn, Chris; Warlick, Erica; Ferguson, Anna; Kasamon, Yvette L.; Borrello, Ivan M.; Hess, Allan; Smith, B. Douglas
Abstract: Myelodysplastic syndromes (MDS) are a heterogeneous group of clonal hematopoietic stem cell malignancies. Currently, approved drugs are given with non-curative intent as the only known cure is allogeneic bone marrow transplantation, which relies on the donor's immune system driving an allogeneic effect. Previous efforts to harness the endogenous immune system have been less successful. We present the results of a pilot study of K562/GM-CSF (GVAX) whole-cell vaccination in MDS patients. The primary objective of safety was met as there were no serious adverse events. One patient had a decrease in transfusion requirements and another demonstrated hematologic improvement suggesting a signal for clinical activity. In vitro correlative studies indicated biological effects on immune cells following vaccination. Although only a pilot study, results are encouraging that an immunotherapeutic approach with a whole-cell vaccine may be feasible in MDS patients.